Aging simulation of thin-film plastics in different environments to examine the formation of microplastic. (1st September 2021) - Chen, Qindong; Wang, Qian; Zhang, Chao; Zhang, Jiawen; Dong, Zihang; Xu, Qiyong
Highlights: TFPs more easily disintegrate to microplastics in water system than on land. Water flow notably affects the production of micro-scale particles. UV affected the structure of plastics via a two-stage process in all environments. Inorganic salts in seawater can promote the chemical aging of plastics. Abstract: Microplastics have received considerable attention in recent years. Understanding the aging mechanism of plastics in different environments (land, fresh water, estuary, and ocean) is critical to control the microplastic formation. Therefore, the aging process of plastics, including polyethylene (PE) and polypropylene (PP), in different environments was simulated by analyzing their physical and chemical structures by using the Raman spectroscopy, scanning electron microscopy, and Fourier transform infrared spectroscopy techniques. After 23 weeks, micro-scale microplastics (size less than 100 μm) could be extracted from the plastic surface through smashing waves in all fresh water and seawater samples. However, complete fragmentation was observed only in the case of thin-film plastics (TFPs, thickness of approximately 10 μm). This phenomenon indicated that TFPs disintegrated to microplastics more easily in the water system than on land, and the water flow notably affected the production of micro-scale particles. Furthermore, ultraviolet radiation affected the chemical structure of plastics through a two-stage process in all environments. In the initial stage, chemical aging occurred in the amorphous regions of both PE and PP, leading to the generation of newly functional groups such as C=O at 1717 cm −1, and a reduced contact angle. In the later stage, PE exhibited additional crystals and increased contact angles, whereas PP demonstrated the tendency of producing oxygen-containing functional groups that could reduce the crystallinity. In addition, several inorganic salts (such as sulfate and phosphorus) in seawater likely combined with C–H-type stretches, thereby promoting the chemical aging of plastics. Graphical abstract: Image, graphical abstract